Assessment of occupational exposure to gaseous peracetic acid - Stefano Dugheri; Alessandro Bonari; Ilenia Pompilio; Marco Colpo; Manfredi Montalti; Nicola Mucci; Giulio Arcangeli (International Journal of Occupational Medicine and Environmental Health, 2018)
Objectives In order to assess short-term exposure to peracetic acid (PAA) in disinfection processes, the Authors compared 4 industrial hygiene monitoring methods to evaluate their proficiency in measuring airborne PAA concentrations.